Parton distribution function uncertainties in theoretical predictions for far-forward tau neutrinos at the Large Hadron Collider - Weidong Bai; Milind Diwan; Maria Vittoria Garzelli; Yu Seon Jeong; Karan Kumar; Mary Hall Reno (Journal of High Energy Physics, 2022)
Abstract New experiments dealing with neutrinos in the far-forward region at the Large Hadron Collider (LHC) are under design or already in preparation. Two of them, FASERν and SND@LHC, are expected to be active during Run 3 and have the potential to detect the interactions of ν and ν ¯ $$ \overline{ν} $$ that come from high-energy collisions in one of the LHC interaction points, extracted along the direction tangent to the beam line. Tau neutrinos and antineutrinos come predominantly from D s ± $$ D_s^{± } $$ production in pp collisions, followed by the leptonic decay of these mesons. Neutrino pseudorapidities in the range of η > 6.9 and η > 8.9 are relevant to these future experiments. At such pseudorapidities at high energies, QCD theoretical predictions for the flux of ν τ plus ν ¯ $$ \overline{ν} $$ τ rely on parton distribution functions (PDFs) in a combination of very small and large parton−x values. We evaluate PDF un certainties affecting the flux of ν τ + ν ¯ $$ \overline{ν} $$ τ produced by D s ± $$ D_s^{± } $$ decay in the far forward region at the LHC. Next-to-leading order (NLO) QCD uncertainties are included in the calculation of D s ± $$ D_s^{± } $$ production and NLO PDF sets are used for consistency. The theoretical uncertainty associated with the 40 PDF sets of the PROSA19 group amounts to ±(20 − 30)% for the (ν τ + ν ¯ $$ \overline{ν} $$ τ ) number of charged-current (CC) events. Scale uncertainties are much larger, resulting in a range of CC event predictions from ~70% lower to ~90% higher than the central prediction. A comparison of the predictions with those obtained using as input the central PDFs from the 3-flavour NLO PDF sets of the CT14, ABMP16 and NNPDF3.1 collaborations show that far-forward neutrino energy distributions vary by as much as a factor of ~2 – 4 relative to the PROSA19 predictions at TeV neutrino energies. The Forward Physics Facility in the high luminosity LHC era will provide data capable of constraining NLO QCD evaluations with these PDF sets.